A Rare Coronary Anomaly: One Ostium Fits All - C. Mihl; B. S. N. Alzand; M. H. Winkens (Cardiology Research and Practice)
Coronary anomalies affect a small percentage of the general population. A solitary coronary ostium in the absence of other major congenital anomalies is very rare. We describe a case of a patient, admitted to our cardiology department with an acute myocardial infarction. A coronary angiogram shows a solitary ostium originating from the right sinus of Valsalva with the left anterior descending coronary artery (LAD) ventral to the pulmonary artery and the circumflex artery (Cx) following its course retroaortically. The theoretical variant of this type of malformation has been described but has not been reported in a clinical case before. Coronary anomalies are usually detected during coronary angiography, but exact course determination and relationships are difficult to visualize. The use of cardiac computed tomography (CCT) allows visualization of the coronary anatomy in a 3-dimensional image and demonstrated an added value to coronary angiography.